Why Do Immunosuppressed Patients with Inflammatory Bowel Disease Not Seem to Be at a Higher Risk of COVID-19? - Scribano, Maria Lia (Dig Dis Sci, 2020)
The COVID-19 pandemic has created a public health emergency. In this context, there are major concerns for patients with inflammatory bowel disease (IBD), particularly for those treated with immunomodulators, biologics, and Janus Kinase inhibitors. Infection susceptibility is, in fact, one of the reported risks for immunotherapy drugs. This review provides the existing evidence from worldwide case series describing: (a) the risk for the SARS-CoV-2 infection and (b) the risk of a severe infection outcome in patients with IBD treated with immunotherapy. Further, the review discusses the potential mechanisms underlying why this group of patients with IBD might be protected from contracting the infection and from a worse disease. From the available data, it appears that these patients should have an enhanced adherence to the recommended preventive measures, suggesting a role in reducing their risk of infection. Furthermore, the immunotherapy may dampen the cytokine storm and inflammation associated with COVID-19. The results of this review seem to confirm that patients with IBD receiving immunomodulators, biologics, or Janus Kinase inhibitors do not have an increased risk of contracting SARS-CoV-2 infection or develop a more severe COVID-19. According to the current evidence, it is advisable to maintain immunotherapy, apart from corticosteroids, in patients with IBD in order to avoid relapse. This review reports only on the cases of patients who tested positive for SARS-CoV-2 by RT-PCR of a nasopharyngeal swab sample. This is a limitation and a more accurate epidemiological picture of the infection will be obtained only via the expanded use of antibody tests.